2006
DOI: 10.1021/bm060494d
|View full text |Cite
|
Sign up to set email alerts
|

Quantification and Confocal Imaging of Protein Specific Molecularly Imprinted Polymers

Abstract: We have employed FITC-albumin as the protein template molecule in an aqueous phase molecular imprinted polymer (HydroMIP) strategy. For the first time, the use of a fluorescently labelled template is reported, with subsequent characterisation of the smart material to show that the HydroMIP possess a significant molecular memory in comparison to that of the nonimprinted control polymer (HydroNIP). The imaging of the FITC-albumin imprinted HydroMIP using confocal microscopy is described, with the in situ removal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 20 publications
2
29
0
Order By: Relevance
“…HydroMIPs were prepared following a previously reported procedure (35) and with the intention of using as little protein sample as possible and at significantly smaller final volumes. For every MIP created, a NIP (nonimprinted polymer) was also created using the same material concentration as the MIP but without the protein template (SI Materials and Methods).…”
Section: Methodsmentioning
confidence: 99%
“…HydroMIPs were prepared following a previously reported procedure (35) and with the intention of using as little protein sample as possible and at significantly smaller final volumes. For every MIP created, a NIP (nonimprinted polymer) was also created using the same material concentration as the MIP but without the protein template (SI Materials and Methods).…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have reported the design and development of aqueous phase molecular imprinting coupled to confocal microscopy imaging, aiming to visualize the imprinting effect (Hawkins et al, 2006). Herein, we have followed the binding of a FITC labelled antibody targeted against 8-OHdG to the surface of the sensor in order to track the 8-OHdG oxidative stress biomarker rebound into the imprinted cavities.…”
Section: Characterization Of the Modified Surfacesmentioning
confidence: 99%
“…6, the binding capacity of NIPM to TMP is relatively small and increases along with the increase of TMP concentration, but for IPM, the binding capacity increases and then gradually reaches a larger equilibrium value. In many binding experiments of templates [18,19], because of the linear increasing of non-selectivity, the relation curve of the binding amount to the initial concentration is often difficult to reach the saturation point. So it could be learned that the adsorption of NIPM to TMP is non-selective, but the adsorption of IPM to TMP is selective.…”
Section: Binding Capacities Of Nipm and Ipm To Tmp At Different Concementioning
confidence: 99%